The Effect of Repetitive Whole Body Cryotherapy Treatment on Adaptations to a Strength and Endurance Training Programme in Physically Active Males - Haq, Adnan; Ribbans, William J.; Hohenauer, Erich; Baross, Anthony W. (Frontiers in Sports and Active Living, 2022)
Despite its potential merit in sport and exercise recovery, the implications of repetitive Whole Body Cryotherapy (WBC) during training programmes require further review due to the possibility of repetitive cold interfering with long term adaptations. This study investigated the impact of two weekly 3 min WBC sessions (30 s at −60°C, 150 s at −120°C) on adaptations to a 6 week strength and endurance training programme. Sixteen male participants (mean ± SD age 33.4 ± 9.8 years, body mass 82.3 ± 9.8 kg) randomly allocated into WBC (n = 7) and non-cryotherapy control (CON, n=9) groups completed the programme consisting of two weekly strength and plyometric training sessions and two weekly 30 min runs (70% VO2 max). Participants were assessed for body fat, VO2 max, muscle torque, three repetition maximum barbell squat and countermovement jump height before and after the programme. Resistance and running intensities were progressed after 3 weeks. Participants in both groups significantly improved muscle torque (WBC: 277.1 ± 63.2 Nm vs. 318.1 ± 83.4 Nm, p < 0.01, d = 0.56; CON: 244.6 ± 50.6 Nm vs. 268.0 ± 71.8 Nm, p = 0.05, d = 0.38) and barbell squat (WBC: 86.4 ± 19.5 kg vs. 98.9 ± 15.2 kg, p = 0.03, d = 0.69; CON: 91.1 ± 28.7 kg vs. 106.1 ± 30.0 kg, p < 0.01, d=0.51) following the 6 week programme. For the CON group, there was also a significant reduction in body fat percentage (p = 0.01) and significant increase in jump height (p = 0.01). There was no significant increase in VO2 max for either group (both p > 0.2). There was no difference between WBC and CON for responses in muscle torque, 3RM barbell squat and body fat, however WBC participants did not increase their jump height (p = 0.23). Repetitive WBC does not appear to blunt adaptations to a concurrent training programme, although there may be an interference effect in the development of explosive power. Sports practitioners can cautiously apply repetitive WBC to support recovery post-exercise without undue concern on athletes' fitness gains or long term performance, particularly throughout training phases focused more on general strength development than explosive power.